Autoethnography as a Strategy for Engaging in Reflexivity - Wilma J. Koopman; Christopher J. Watling; Kori A. LaDonna (SAGE Publishing, 2020)
Reflexivity is a key feature in qualitative research, essential for ensuring rigor. As a nurse practitioner with decades of experience with individuals who have chronic diseases, now embarking on a PhD, I am confronted with the question "how will my clinical experiences shape my research?" Since there are few guidelines to help researchers engage in reflexivity in a robust way, deeply buried aspects that may affect the research may be overlooked. The purpose of this paper is to consider the affordances of combining autoethnography (AE) with visual methods to facilitate richer reflexivity. Reflexive activities such as free writing of an autobiographical narrative, drawings of clinical vignettes, and interviews conducted by an experienced qualitative researcher were analyzed to probe and make visible perspectives that may impact knowledge production. Two key themes reflecting my values-fostering advocacy and favoring independence and autonomy were uncovered with this strategy.